BENEISH RATIO INDEX SEBAGAI ALAT DETEKSI KECURANGAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR - Zulzilawati, Zulzilawati; Wahyuni, Nanik (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The purpose of this study is to determine the number and detect companies that commit fraud so that companies can be categorized as manipulators, non-manipulators and gray companies. This research uses quantitative research with descriptive approach. The object used in this study is a Manufacturing Company listed on the Indonesia Stock Exchange (IDX) in 2016-2019. The research sample was taken using purposive sampling technique. This study analyzes data using eight types of financial ratios contained in the Beneish Ratio Index method. The results showed that the manufacturing companies classified as the most manipulators in 2017. Then the manufacturing companies classified as the most non-manipulators in 2019 were 52 companies. Furthermore, the largest number of manufacturing companies classified as gray companies in 2016 and 2018 were 5 companies.